PKM SOSIALISASI PEMANFAATAN SAMPAH ORGANIK DI SD NEGERI 1 PEREAN KANGIN, BATURITI, TABANAN, BALI - Meinarni, Ni Putu Suci; Winatha, Komang Redy; Yasa, I Putu Pedro Kastika; Semara, Arya Aditya Widya (Empowerment : Jurnal Pengabdian Masyarakat, 2019)
AbstractSD Negeri 1 Perean Kangin is a partner in the Community Partnership Program, which is one of the state primary schools located in the Baturiti Tabanan area, where the environment around the school is still a beautiful rural environment with little technological development. The problem faced is the lack of awareness of the potential of organic waste contained in their environment, and knowledge of the importance of sorting rubbish, which still piles up various types of garbage in one trash can. The purpose of this activity is to increase awareness and increase students' knowledge and skills to sort and manage waste, especially organic waste. The presentation method is used to describe in general the concept of waste segregation and by staying interactive with students. The material presented is the difference between organic and inorganic waste, and how to use it according to the type of waste, and the results of organic waste management. The results of activities that have been carried out are the presentation of material on organic and inorganic waste, as well as training in making compost as a result of organic waste processing. Based on the activities that have been carried out students are able to sort waste according to its type.Keywords: Environment, Community Partnership Program, Waste, Compost Fertilizer.Â AbstrakSD Negeri 1 Perean Kangin adalah mitra dalamProgram Kemitraan Masyarakat yang merupakan salah satu sekolah dasar negeri yang terdapat di daerah Baturiti Tabanan, dimana lingkungan disekitar sekolah merupakan lingkungan pedesaan yang masih asri dengan terpengaruh sedikit perkembangan teknologi. Masalah yang dihadapi adalah kurangnya kesadaran terhadap potensi sampah organik yang terdapat di sekitar lingkungan mereka, dan pengetahuan tentang pentingnya pemilahan sampah, yang masih menumpuk sampah berbagai jenis dalam 1 tempat sampah. Tujuan kegiatan ini adalah untuk meningkatkan kesadaran dan menambah pengetahuan dan keterampilan siswa untuk memilah dan mengelola sampah khususnya sampah organik. Metode presentasi digunakan untuk menjabarkan secara umum konsep pemilahan sampah dan dengan tetap interaktif dengan siswa. Adapun materi yang disampaikan adalah perbedaan sampah organik dan an organik, serta cara pemanfaatannya sesuai dengan jenis sampah, dan hasil dari pengelolaan sampah organik. Hasil kegiatan yang sudah dilaksanakan adalah pemaparan materi tentang sampah organik dan an organik, serta pelatihan pembuatan pupuk kompos sebagai hasil dari pengolahan sampah organik. Berdasarkan kegiatan yang sudah dilakukan siswamampu untuk memilah sampah sesuai dengan jenisnya.Kata Kunci: Lingkungan, Program Kemitraan Masyarakat, Sampah, Pupuk Kompos.